Sporadic Hemangioblastoma of the Kidney: a rare renal tumor - Liu Yang; Qiu Xue-shan; Wang En-Hua (BMC, 2012)
Abstract Hemangioblastoma is a benign and morphologically distinctive tumor that can occur sporadically or in association with von Hippel-Lindau disease in approximately 25% of the cases, and which involves the central nervous system in the majority of the cases. Rare occurrences of hemangioblastoma in peripheral nerves and extraneural tissues have been reported. This report describes one case of sporadic renal hemangioblastoma happened in a 16-year-old Chinese female patient, presenting with hematuria, and low back pain. Histologically, the tumors were circumscribed, and composed of sheets of large polygonal cells traversed by arborizing thin-walled blood vessels. The diagnosis of hemangioblastoma was confirmed by negative immunostaining for cytokeratin, and positive staining for α-inhibin, S100 and neuron-specific enolase (NSE). This benign neoplasm which can be mistaken for various malignancies such as renal cell carcinoma, epithelioid hemangiopericytoma and epithelioid angiomyolipoma, deserves wider recognition for its occurrence as a primary renal tumor. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/5445834246942699